2019
DOI: 10.24003/emitter.v7i1.365
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Productivity of Wire Electrical Discharge Machining Toward Sustainable Production by using Artificial Neural Network Modelling

Abstract: Sustainability plays an important role in manufacturing industries through economically-sound processes that able to minimize negative environmental impacts while having the social benefits. In this present study, the modeling of wire electrical discharge machining (WEDM) cutting process using an artificial neural network (ANN) for prediction has been carried out with a focus on sustainable production. The objective was to develop an ANN model for prediction of two sustainable measures which were material remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The work by [47] uses ANN technology to develop a predictive model of sustainability measures that improve the quantity and quality of production. They developed a model based on artificial intelligence that delivers an accurate and efficient forecast, indicating that the constructed model has a high level of accuracy in predicting sustainable measures.…”
Section: Measuring and Controlling Sustainabilitymentioning
confidence: 99%
“…The work by [47] uses ANN technology to develop a predictive model of sustainability measures that improve the quantity and quality of production. They developed a model based on artificial intelligence that delivers an accurate and efficient forecast, indicating that the constructed model has a high level of accuracy in predicting sustainable measures.…”
Section: Measuring and Controlling Sustainabilitymentioning
confidence: 99%
“…Some findings concerning the effect of machining methods on surface morphology and stereo-metric surface parameters in wire-EDM of hard machined materials which also include Inconel alloys, are discussed [16]. Simultaneously, several studies can be reported in literature that discusses the challenges correlated with precision machining of different materials with wire-EDM [17]. The findings of magnesium alloy in view of efficient machining operation with different facets of the performance and reliability of the magnesium alloy are discussed using wire-EDM [18], [19].…”
Section: Related Workmentioning
confidence: 99%